Learning Technology : a complete guide for learning professionals - Clark, Donald author (London, United Kingdom: New York, USA: Kogan Page Limited, 2023)
"Learning technology is now an integral part of all learning and development (L&D) activity. Understanding what these technologies, are, how they work and their aims is key to successful L&D practice. Learning Technology is written by a leading voice in the learning tech industry with over 35 years' experience. It explains the history of learning tech, its aims, its introduction to the workplace and the benefits to both the individual and the business. This book covers everything from online and mobile learning, simulations and gamification as well as detailed discussion of Learning Management Systems (LMSs), Learning Experience Platforms (LXPs) and Learning Record Stores (LRSs). This book also highlights the importance of data and analytics and covers the latest developments in the learning technology space including artificial intelligence, virtual reality and the metaverse. Most importantly, Learning Technology helps L&D professionals assess where their budget is best spent on technology and explains how to analyse the return on investment (ROI). Full of examples and practical advice throughout, this book also includes case studies from organizations including British Airways, UK National Health Service (NHS) and Learning Pool"--
Learning technology -- Prehistoric learning technology -- Writing -- Printing and books -- Broadcast and media -- Teaching technology -- Teaching machines -- Computers and Internet -- Platforms -- Content -- Artificial intelligence -- Metaverse.
Includes index.
Keywords: Educational technology; Mass media in education; Computer-assisted instruction; Telecommunication -- History